Gender diversity in autistic clients: an ethical perspective - Glaves, Katie Jo; Kolman, Leah (Frontiers in Psychiatry, 2023)
Autonomy and dignity are key ethical principles in psychiatric and psychological codes of ethics. Yet, when working with autistic individuals who are transgender/gender non-conforming (TGNC), non-autistic and cisgender clinicians can unintentionally take away client dignity and autonomy by disbelieving or stigmatizing clients’ gender identities. Lack of awareness or discomfort around autism and gender dysphoria can lead clinicians to assumptions and interventions that damage both client rapport and client mental health; discouraging clients from being honest with clinicians about their mental health, and potentially leading to harm. Clinicians must take an intersectional view of their autistic clients’ gender identities to reduce stigma and recognize the needs of the whole person. Facilitating access to gender-affirming care is an important part of caring for TGNC clients, including those who are autistic. The authors will discuss the ethical imperative to help autistic clients access gender-affirming care, while discussing common concerns clinicians have when helping autistic clients access this care, as well as the need to believe and support autistic clients when they share their gender identities with clinicians.